CRITICAL REVIEW STUDY ON CONTRIBUTION OF YOGA IN SPORTS (International Journal of Ayurveda and Pharma Research, 2017)
Every sports person in his career suffers from various sports injuries. Here treatment required is faster and long lasting. Recently research studies proved that Yoga are very effective in sports, health and fitness related fields such as aerobic training, strength training, body building, and endurance sports. A combined approach of Ayurveda, physiotherapy and Yoga can be successfully employed sports, for training sports person, treating injuries and rehabilitation. Yoga is useful for all type of sports to help prevent injuries. One gets extra agility which avoid damage, provides more strength and improves a players ability to react to a situation. Yoga works not only at physical level but also at psychological level, ensuring well-rounded development. Yoga can benefit professional sports person, it is necessary to explore What kind of sport required to play and play it well. So we can say that Yoga is very beneficial to everyone specially for a sportsman.